Analogic and symbolic dimensions in graphic representations associated with patient information leaflets for medicines. Issue 5 (20th October 2022) - Cohen, Golda; Moliner, Pascal
Abstract : The aim of the present study was to assess the mental images associated with different categories of patient medical information, depending on literacy level. 52 participants divided into two groups (high vs. low literacy) were asked to draw the first picture that came to mind after reading or hearing information taken from leaflets supplied with medication. There were 16 items of information in total. The drawings were analysed using a symbolism grid. Results suggest that each group produced specific visual representations of the information items. Participants in the high-literacy group tended to draw symbolic forms to illustrate the medical information, while those in the low-literacy one mainly produced concrete forms. Each group had its own set of canonical forms. These findings underscore the need to use health pictograms in medical practice, providing they correspond to the social representations of individuals with low literacy, to ensure optimum treatment adherence and reduce the risk of misunderstandings.